Sagot :
[tex]x^2 - 5x + k[/tex]
a = 1; b = -5 ; c = k?
k = (b/2)^2
= (-5/2)^2
k = 25/4 or
= [tex]6 \frac{1}{4}[/tex]
a = 1; b = -5 ; c = k?
k = (b/2)^2
= (-5/2)^2
k = 25/4 or
= [tex]6 \frac{1}{4}[/tex]
x²-5x+k
x=⁻b+(b₋4ac)
----------------
2(a)
x=5+√(5²-4(1)(1)
-------------------
2(1)
x=5+√25-4
-------------
2
x=5+√21
----------------
2
x=5+11
-----------
2
x=5+11
-----------
2
x=15
-------
2
x₁=7.5
x=5-11
---------
2
x=⁻6
--------
2
x₂=⁻3
x₁=7.5 and x₂=⁻3
x=⁻b+(b₋4ac)
----------------
2(a)
x=5+√(5²-4(1)(1)
-------------------
2(1)
x=5+√25-4
-------------
2
x=5+√21
----------------
2
x=5+11
-----------
2
x=5+11
-----------
2
x=15
-------
2
x₁=7.5
x=5-11
---------
2
x=⁻6
--------
2
x₂=⁻3
x₁=7.5 and x₂=⁻3